(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The cornerstones of sustainable agriculture addressing critical concerns such as food security, environmental degradation, and climate change encompass crop ecology, agroforestry, and regenerative farming. This summary provides an overview of the core concepts within these domains.